Socio-emotional learning in Argentinean early childhood education curricula - Dall'Asta, Juan Cruz (2024)
The aim of this study was to investigate Socio-Emotional Learning (SEL) in the curricula of Early Childhood Education in Argentina, and the expected out-comes of SEL into practice. For this purpose, the totality of 24 provincial cur-ricula were selected corresponding to the same number of educational jurisdic-tions in Argentina. After a first step of analysis, 10 curricula were studied us-ing CASEL framework (2020) as the theoretical lens to identify the appearance of SEL concepts, compare definitions with the international literature, and ex-plore the expected outcomes related to teaching and learning. The research questions that guided this study were: (1) How is Socio-Emotional Learning expressed in the curricula? and (2) What kind of expected outcomes in relation to SEL are determined by the curricula? The methods utilized to answer these questions were quantitative and qualitative content analysis. Results showed, in terms of appearance, a variety of SEL conceptualizations within the data. Among the findings, there were exact coincidence with the theoretical lens (CASEL framework) in naming and definition, and different naming with simi-lar definitions to the ones proposed by the literature background. Regarding the outcomes expectations and practical application of these skills, Argentinean curricula in ECE showed that SEL was viewed as a community-oriented set of abilities.